Flow Characteristics of Flapping Motion of a Plane Water Jet Impinging onto Free Surface (Advances in Applied Mathematics and Mechanics, 2021)
A submerged turbulent plane jet in shallow water impingingvertically onto the free surface will produce a large-scale flappingmotion when the jet exit velocity is larger than a critical one. Theflapping phenomenon is verified in this paper through a large eddysimulation where the free surface is modeled by volume of fluidapproach. The quantitative results for flapping jet are found to bein good agreement with available experimental data in terms of meanvelocity, flapping-induced velocity and turbulence intensity.Results show that the flapping motion is a new flow pattern withcharacteristic flapping frequency for submerged turbulent planejets, the mean centerline velocity decay is considerably faster thanthat of the stable impinging jet without flapping motion, and theflapping-induced velocities are as important as the turbulentfluctuations.